Nilai-Nilai Religius Dalam Novel Buya Hamka Karya Ahmad Fuadi Dan Implikasinya Dalam Pembelajaran Teks Novel Di SMA - Rani Ayunda; Abdurahman Abdurahman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study is to describe and explain religious values in the form of religious values 1) worship values, 2) jihad values, 3) sincere values, 4) moral values in the novel Buya Hamka by Ahmad Fuadi. The formulation of the problem in this study is how religious values are contained in the novel Buya Hamka by Ahmad Fuadi. This type of research is qualitative with descriptive research methods. The data in this study are words, groups of words, and sentences in which there are religious values in the novel Buya Hamka by Ahmad Fuadi. The source of data in this study is the novel Buya Hamka by Ahmad Fuadi. The instrument in this study is the researcher himself. The data collection technique carried out in this study is an observation technique. The observation used is a type of non-participant observation. The data validation technique in this study is a detailed description technique. Data is analyzed by steps, namely (1) data reduction, (2) data presentation, (3) data verification. Based on the results of the study, it was concluded that the religious values studied in the novel Buya Hamka by Ahmad Fuadi found 257 data divided into four types of religious values. First, there are 66 data containing the value of worship, with indicators of performing prayers, giving thanks, making dhikr. Second, there are 77 data containing jihad values. Third, there are 11 data that contain sincere value. Fourth, there are 103 data containing akhalak values. In the novel Buya Hamka by Ahmad Fuadi, the most prominent religious value is morals, with indicators of morals to Allah, morals to oneself, morals to the family, morals to society.